3D ferromagnetic graphene nanocomposites with ZnO nanorods and Fe3O4 nanoparticles co-decorated for efficient electromagnetic wave absorption. (1st March 2018) - Zhang, Na; Huang, Ying; Wang, Mingyue
Abstract: The nanocomposites of combining magnetic nanoparticles with dielectric materials are highly desirable for high performance electromagnetic (EM) wave absorbers due to their great impedance matching property. In this work, 3D ferromagnetic graphene nanocomposites with ZnO nanorods and Fe3 O4 nanoparticles co-decorated have been successfully synthesized via a facile solvothermal process in combination with the co-precipitation route, and the EM wave absorption performance is first reported. The maximum reflection loss (RL ) of the 3D RGO/Fe3 O4 /ZnO nanocomposites reaches −57.0 dB at 13.5 GHz with a matching thickness of only 2.0 mm. The effective absorption bandwidth with the RL less than −10 dB can be tuned to 10.8 GHz (5.9–16.7 GHz) at the absorber thickness of 1.5–4.0 mm, which covers the whole X band. These results suggest that the 3D nanocomposites possess the advantages of thin thickness, broad bandwidth, lightweight and strong absorption, and can be used as promising materials for stealth camouflage techniques. Graphical abstract: